2013
DOI: 10.1016/j.biocel.2012.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Period 2 in myocardial ischemia: Clinical implications of a light dependent protein

Abstract: Since the onset of myocardial infarction and stroke has distinct circadian patterns, the disruption of circadian rhythms may contribute to cardiovascular disease. A recent clinical study, reporting that the severity of myocardial ischemia depends on the time-of-day when ischemia occurs, highlights the impact of circadian rhythms on cardiovascular disease. In support of these observations, we found a cardioprotective role of the circadian rhythm protein Period 2 (Per2) during myocardial ischemia in mice. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
1
37
0
3
Order By: Relevance
“…Our recent studies found an important role of light elicited Per2 in controlling glycolysis during myocardial ischemia [10, 12, 23]. To understand a potential role of miR-21 in glycolysis, we first performed loss of function (LOF) studies using miR-21 inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies found an important role of light elicited Per2 in controlling glycolysis during myocardial ischemia [10, 12, 23]. To understand a potential role of miR-21 in glycolysis, we first performed loss of function (LOF) studies using miR-21 inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Peripheral tissues display oscillations in circadian rhythm protein expression similar to those of the brain, 12,13 likely through secreted signaling molecules (Figure 1). 10,14,15 …”
Section: Circadian Rhythms: ‘External Cues’ Vs ‘Internal Clock’mentioning
confidence: 99%
“…The primary control of the circadian clock is located in the hypothalamic suprachiasmatic nuclei (SCN), which are used to synchronize peripheral clocks in organs and tissues [13], [14]. This synchronization is accomplished through a series of tightly regulated circadian genes such as Clock, Brain and muscle Arnt-like protein-1 (Bmal1)[15], Neuronal PAS domain protein 2 (Npas2), Cryptochrome (Cry1/2), and Period (Per1/2). Mutations in or knockout of these circadian genes lead to diverse pathophysiological disorders, including metabolic syndrome, obesity [16], premature aging [17], and abnormal sleep cycle [18].…”
Section: Introductionmentioning
confidence: 99%